EFEK EKSTRAK BUAH ROSELA (HIBISCUS SABDARIFFA L.) TERHADAP KUANTITAS DAN KUALITAS SPERMA MENCIT (MUS MUSCULUS L.) YANG DIINDUKSI NIKOTIN DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Amanda Rahmaniah Putri; Lucia Maria Santoso; Kodri Madang (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2015)
Â  Abstract: This research aimed to know the potential of ethanol extract of roselle fruits in improving the quantity and quality of sperm in mice induced nicotine. The method is implemented with the experimental method that uses a completely randomized design 30 male mice. This study consists of five treatments and six replications. Treatment for the provision of nicotine with a dose of 0,07mg / 10 g body weight and roselle fruit ethanol extract at a dose consisting of 0 mg / 10 g BB, 3 mg / 10 g BB, 6 mg / 10 g BB, and 9 mg / 10 g BB. Roselle fruit extract given by gavage and nicotine via subcutaneous injection for 35 days. Parameters measured were the number, viability, normal morphology, motility, and sperm plasma membrane integrity. The data were analyzed by analysis of variance and real distance difference test (BJND). The average number of sperm in mice P1, P2, P3, and P4 is 103.17 x 106 / ml, 153 x 106 / ml, 157 x 106 / ml, 146 x 106 / ml. The percentage of sperm viability in mice P1, P2, P3, and P4 is 47%, 60.67%, 70%, 68.67%. The percentage of normal sperm morphology P1, P2, P3, and P4 is 42.5%, 59.5%, 73.67%, 62.83%. The percentage of sperm motility in mice P1, P2, P3, and P4 is 41.3%, 61%, 63.7%, 59%. The percentage of plasma membrane integrity mice P1, P2, P3, and P4 is 42.4%, 70.4%, 71%, 62.9%. The results showed that ethanol extract of roselle fruits at a dose of 3 mg / 10 g BB maximal increase the number, the percentage of normal morphology, the percentage motility, sperm plasma membrane integrity mice and 6 mg / 10 g BB increased the percentage of sperm viability nicotine-induced mice. Results of this study are expected to be additional material on learning Biology Semester II Class X Basic Competencies 3.3 Describe the characteristics Divisio and its Role in the World of Plants for Survival on Earth. Keywords: quantity and quality of mice sperm, roselle, nicotine